(untitled) (International Journal of Medical and Surgical Sciences, 2019)
Anxiety is understood as a response to situations in which the source of threat for the individual is uncertain, ambiguous or objectively absent. Three factors seem to unleash the anxiety process: novelty, insecurity and expectation. People with dental fear often have poor oral health, being fear and anxiety the reasons for not visiting the dentist regularly. This circumstance hinders dental care and might even lead to preventing dental care for some individuals. The aim of this article is to correlate fear and anxiety in a sample of Chilean 7-to-10-year-old children and their parents/guardians. FIS and CFSS-DS correlation was not significant (r=0.1785; p=0.1065). No correlation was found between child anxiety level and caries experience: dmft/FIS (r=-0.0312; p= 0.7796), DMFT/FIS (r=-0.1632; p=0.1404). Likewise, no correlation was found between parental and child anxiety levels measured by FIS (r=0.0527; p=0.6074) nor CFSS-DS (r=-0.0498; p=0.6549). A significant correlation was found between parents’ schooling level and REALD-30 (r=0.3870; p=0.003), but none between the latter and M-DAS (r=0.0254; p=0.8198). Low correlation between these methods seems to be justified by the multidimensional character of anxiety, which presents physiological, cognitive and motor reactions that are manifested differently in each individual.